The Influence of Ethical Leadership, Creative Work Climate, and Self-Efficacy on Employee Performance with Knowledge Sharing as an Intervening Variable - Cut Chandrika; Irma Setyawati (International Journal of Social Service and Research, 2023)
Performance is the main thing that an organization expects from the human resources it manages to bring the organization to its vision. In terms of employee performance, public service organizations have so far not yet succeeded in sufficing community expectations. This study aims to determine the effect of ethical leadership, creative work climate, and self-efficacy on employee performance and the role of knowledge sharing as a mediating variable. The research sample consisted of 100 employees at the Central Office of the Ministry of Industry with simple random sampling. The research approach is a quantitative method. The research instrument used the Individual work performance questionnaire (IWPQ), Ethical Leadership Scale, Creative Climate Questionnaire (CCQ), General Self-Efficacy Scale (GSE), and knowledge sharing measurement based on a combination of social capital factors and theory of reasoned action, all of which were modified and adapted to the needs of this research. Data collection techniques were carried out by interviews and closed questionnaires with a Likert scale of 1 to 4 with data analysis techniques using Smart PLS 4. The research findings show that ethical leadership, creative work climate, and self-efficacy have a direct positive and significant effect at the moderate level on knowledge sharing, and shows that ethical leadership, creative work climate, and self-efficacy have a direct positive and significant effect at a strong level on employee performance. Unexpected results reveal that the mediating role of knowledge sharing between the influence of ethical leadership, creative work climate, and self-efficacy on employee performance is negatively significant at a low level.